Cardiology service of the south federal region: problems and perspectives - L. I. Katelnitskaya (Российский кардиологический журнал)
The South Federal Region (SFR) is characterized by unfavorable demographic situation, reflecting general situation in the whole country. For 2004, disease incidence in SFR has increased by 8, 7 %, and disease prevalence - by 7, 8 %. Mortality was high in all SFR subjects. In-hospital mortality (SFR, 2005) due to cardiovascular disease (CVD) was 3, 22 per 100 admitted patients, 15, 9 - for acute myocardial infarction, 7, 09 - due to cerebrovascular pathology, 4, 11 - for chronic coronary heart disease, and 0, 13 - due to high blood pressure. Prevalence of dispanser follow-up among CVD patients was 31, 77 % in 2002, 31, 29 % in 2003, 30, 96 % in 2004, and 31, 4 % in 2005. Taking into account the need for the National Health Project realization, the problems of hospital bed restructuring, health workers' professional level improvement, and preventive technology implementation are most actual.